PROGNOSTIC VALUE OF PROTEASE ACTIVATED RECEPTOR-1 IN EGYPTIAN CHILDREN WITH ACUTE LYMPHOBLASTIC LEUKEMIA - Hagag, Adel Abd Elhaleim (Mediterranean Journal of Hematology and Infectious Diseases, 2014)
Background: Acute Lymphoblastic leukemia (ALL) is a malignant disorder of lymphoid progenitor cells that proliferate and replace the normal hematopoietic cells of the bone marrow. Protease-activated receptor 1 (PAR-1), is atypical member of this family of receptors that mediate cellular responses to thrombin and related proteases. PAR1 is expressed by a wide range of tumor cells and can promote tumor growth, invasion and metastasis. The aim of this work was to study the role of PAR-1 expression in newly diagnosed ALL patients. Patients and methods: This study was conducted on 44 children with newly diagnosed ALL who were admitted to Hematology Unit, Pediatric department, Tanta University Hospital including 24 males and 20 females with their age ranged from 4-17 years and their mean age value of 9.06±3.26 who were divided into two groups; PAR-1 positive group (18 patients) and PAR-1 negative group (26 patients). All patients were subjected to complete history taking, thorough clinical examination, bone marrow aspiration and flow cytometric analysis for detection of PAR-1 expression by malignant cells. Results: PAR-1 was positive in 18 cases (41%) and negative in 26 cases (59%) of studied patients. This study showed no significant relation between PAR-1 expression and age, sex and most of the clinical data including hepatomegaly, splenomegaly and purpura while generalized lymphadenopathy was significantly higher in PAR-1 positive group. PAR-1 positive expression was associated with some bad prognostic laboratory parameters including higher hemoglobin, higher white blood cells, higher peripheral blood and bone marrow blast cells, higher serum LDH and lower platelets count. No significant association was detected between PAR-1 expression and immunophenotyping. There were significantly higher remission rates in PAR-1 negative group and significantly higher relapse and death rates in PAR-1 positive group. Conclusion: From this study, it could be concluded that PAR-1 expression on ALL cells represents an important adverse prognostic factor. Recommendations: PAR-1 expression should be routinely investigated for better prognostic assessment of ALL patients at diagnosis and should be taken in consideration in designing future therapeutic strategies based on patients- specific risk factors.